2008
DOI: 10.1021/jp0746650
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of 1-Butyl-3-methylimidazolium Tetrafluoroborate + Water Mixtures Studied by Infrared Vibrational Spectroscopy

Abstract: Mixtures of ionic liquid (IL, 1-butyl-3-methylimidazolium tetrafluoroborate, [BMIM][BF4]) and water with varying concentrations were studied by attenuated total reflection infrared absorption and Raman spectroscopy. Changes in the peak intensities and peak positions of CHx (x = 1, 2, 3) vibration modes of the cation of the IL and OH vibration modes of the water molecules were investigated. Peaks from normal-mode stretch vibrations of CH bonds belonging to the imidazolium ring of the cation did not change their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
220
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(241 citation statements)
references
References 50 publications
18
220
1
2
Order By: Relevance
“…The spectrum, in its general structure, resembles that for [BMIM]BF4, discussed in some detail in Ref. 29 although the structure of the two groups centred around 2900 and 2980 cm -1 appears to be slightly more complicated in the present case.…”
Section: Assignment Of Spectral Structuressupporting
confidence: 59%
See 1 more Smart Citation
“…The spectrum, in its general structure, resembles that for [BMIM]BF4, discussed in some detail in Ref. 29 although the structure of the two groups centred around 2900 and 2980 cm -1 appears to be slightly more complicated in the present case.…”
Section: Assignment Of Spectral Structuressupporting
confidence: 59%
“…1), we were guided by the Fourier transform infrared spectroscopy (FTIR) and Raman results on liquid [EMIM]Tf2N. 21,[24][25][26][27][28][29] Accordingly, the aliphatic C-H modes of the CH2 group, the CH3 terminal group of the ethyl chain, and the CH3 group bonded to the [EMIM] ring are seen between 2850 and about 3000 cm -1 . The spectrum, in its general structure, resembles that for [BMIM]BF4, discussed in some detail in Ref.…”
Section: Assignment Of Spectral Structuresmentioning
confidence: 99%
“…[6][7][8][9][10] Based on thermodynamic parameters, such as excess chemical potentials and excess partial molar enthalpies and entropies, aggregations of 1-butyl-3-methlyimidazolium tetrafluoroborate (BMI + BF4 -) and BMI + iodide (BMI + I -) in aqueous solutions have been discussed. 6 This study revealed that the ILs form clusters in the range of IL mole fraction xIL > ~0.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, aggregation of BMI + BF4 -in aqueous solutions has been discussed on the basis of the C-H vibration modes for the alkyl groups within imidazolium cation by means of attenuated total reflection infrared and Raman spectroscopy. 10 In contrast to IL-water mixtures, there have been a few reports on aggregation behavior of ILs in nonaqueous molecular liquids. …”
Section: Introductionmentioning
confidence: 99%
“…It has already been established that BMIM + in BMIM + BF4 -and/or other ionic liquids involves two conformers with respect to the alkyl group of BMIM + (trans-trans and gauche-trans BMIM + ) in equilibrium, and the two conformers almost equally exist in neat ionic liquids. [24][25][26] The conformer ratio in the BMIM + BF4 -/ water system, however, changes with the mixing ratio of the mixed solvents, 27 but the equilibrium constants between the conformers are not known yet. Thus, it is difficult to obtain the correct value of gintra(r) for BMIM + in binary mixtures.…”
Section: From the Observed G(r)mentioning
confidence: 99%